New data on Cladocera (Crustacea: Branchiopoda) of Peninsular Malaysia - Sinev, Artem Y.; Dadykin, Ivan A.; Umi, Wahidah A.d.; Yusoff, Fatimah M. (Zootaxa, 2025)
Cladoceran samples from Peninsular Malaysia were collected during four sampling trips: in October 2013, November–December 2014, January–February 2018, and September 2022. More than 50 localities were sampled on each trip, including ditches, canals, rivers, ponds, swamps, lakes, old mining pools, and reservoirs. In these samples, we revealed six species new to Malaysia: two of them are planktonic (Bosmina meridionalis and Bosmina fatalis) and four are substrate-associated (Simocephalus expinosus, Anthalona spinifera, Anthalona vandammei, Karualona serrulata). Both species of the genus Bosmina appear to be recent additions to the local fauna, as this genus was not recorded in Malaysia until the last decade. New records are obtained on three rare local species: Simocephalus mixtus, Streblocerus spinulatus, and Acroperus harpae. The morphology of two uncommon East Asian species, Coronatella acuticostata and Chydorus obscurirostris tasekberae was investigated in detail for the first time. With the new records, the list of valid cladoceran species of Malaysia now consists of 72 species as compared to 62 species reported by Idris (1983) in his monograph. However, more studies are needed to produce an exhaustive final species list of the Malaysian cladocerans.